Endoscopic ultrasound–guided FNA and ProCore biopsy in sampling pancreatic and intra‐abdominal masses. Issue 2 (2nd October 2015) - Dwyer, Jessica; Pantanowitz, Liron; Ohori, N. Paul; Pai, Reetesh K.; Vrbin, Colleen; Brand, Randall E.; Monaco, Sara E.
Abstract : BACKGROUND: ProCore fine‐needle biopsy (FNB) was introduced to improve the diagnostic yield of endoscopic ultrasound (EUS)–guided fine‐needle aspiration (FNA) sampling. The aim of this study was to evaluate EUS‐guided sampling of intra‐abdominal masses and compare the diagnostic utility of conventional EUS‐FNA and ProCore FNB. METHODS: EUS‐guided biopsy samples (FNA and/or EchoTip ProCore FNB) were retrospectively retrieved over the course of 23 months. Clinical findings, pathology reports, and available histological materials were reviewed. All cell blocks were reviewed, and their cellularity was scored (range, 0‐3). RESULTS: Fifty‐six masses from 58 cases were acquired, and they included 40 pancreatic sites and 16 other intra‐abdominal sites. Among the 31 FNB‐only cases, 71% were satisfactory, 65% were positive for malignancy at the time of final diagnosis, and their cell blocks were moderately cellular. For the cases with both FNB and FNA performed, more FNB samples than FNA samples were satisfactory (83% vs 76%) and were positive for malignancy (65% vs 48%) at final diagnosis, and the former had more cellular cell blocks (mean score, 1.58 vs 1.29); however, the differences were not statistically significant. Significantly more FNB samples were used for immunostains (48% vs 10%; P  = .005). CONCLUSIONS: These data show that a wide variety of intra‐abdominal masses were amenable to sampling by ProCore FNB. In this subset of cases with prior/concurrent indeterminate FNAs, FNB showed slightly better diagnostic yield, and had more cellular tissue samples and more material for ancillary studies than matched FNAs. Cancer (Cancer Cytopathol) 2016;124:110–121. © 2015 American Cancer Society . Abstract : The use of ProCore fine‐needle biopsy in the evaluation of a variety of solid intra‐abdominal masses sampled via endoscopic ultrasound is described. Overall, in a subset of cases that are difficult to diagnose by fine‐needle aspiration alone, ProCore fine‐needle biopsy is associated with greater cellularity and hence more material for ancillary studies and is consequently associated with more satisfactory specimens in comparison with matched fine‐needle aspiration samples.